Enhancing Efficiency in Healthcare through Automation of Repetitive Tasks and Rapid Data Analysis for Lead Time Reduction - Lastiar Melanie Fiorella; Putri Alya Kamila; Wynd Rizaldy; Ika Utami Yulihapsari (Green Publisher, 2025)
This study highlights the critical importance of reducing lead time for healthcare clients, given their need for quick product rotations and the complexity involved in picking and delivering healthcare products. Challenges such as supply and demand unpredictability and third-party payer issues necessitate adjustments in lead time for custom orders, which require extensive communication and resource management. The study uses a systematic literature review that aims to enhance efficiency by reducing lead time through the automation of repetitive tasks and rapid data analysis to meet customer satisfaction in the healthcare industry. This study will use quantitative methods and Lean Six Sigma to achieve these improvements. The results indicate that improving workflows and managing production schedules are essential for meeting deadlines and ensuring product quality and customer satisfaction.